2003
DOI: 10.1046/j.1365-2427.2003.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Are biological classifications of headwater streams concordant across multiple taxonomic groups?

Abstract: Summary 1. Studies assessing human impacts on freshwater ecosystems are typically based on a single taxonomic group, often macroinvertebrates or fish. Unfortunately, the degree to which such macroinvertebrate or fish‐based surveys can be generalised across other taxonomic groups remains largely unknown. A prerequisite for useful generalisations is that different taxonomic groups exhibit concordant patterns of community structure across sites. 2. We examined the concordance among fish, benthic macroinvertebrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
76
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 47 publications
8
76
0
2
Order By: Relevance
“…In other words, the data in our study came from a large spatial scale composed of five large river watershed and many small basins on the national scale. Thus, the current data support the idea that concordance could be found on a large spatial scale; however, concordance was not observed on a small scale, as proposed by Paavola et al (2003). Allen et al (1999) hypothesized a strong concordance with a similar body size of taxa.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In other words, the data in our study came from a large spatial scale composed of five large river watershed and many small basins on the national scale. Thus, the current data support the idea that concordance could be found on a large spatial scale; however, concordance was not observed on a small scale, as proposed by Paavola et al (2003). Allen et al (1999) hypothesized a strong concordance with a similar body size of taxa.…”
Section: Discussionsupporting
confidence: 82%
“…However, diatoms did not show significant correlation with macroinvertebrates. Meanwhile, previous studies have revealed low assemblage concordance in streams at within-basin scales (Allen et al, 1999;Paavola et al, 2003). These differences may be due to the differences of spatial scale in the study area.…”
Section: Discussionmentioning
confidence: 70%
“…This suggests a very important role of macrofungi in semi-natural, unstable phytocoenoses, whose existence depends on intensive human activity (exploitation as pastures, and mowing of grasses). The IndVal is a particularly effective tool for ecological bioindication (MacGeoch et al 2002;Paavola et al 2003;Penczak 2009). The results of the present mycological investigations of xerothermic swards demonstrate the value of macrofungi as bioindicators that can be useful in the practical conservation of rare and endangered plant communities.…”
Section: Discussionmentioning
confidence: 99%
“…In a second study, Heino et al (2003) found low concordance in species richness of larvae from four groups in headwater streams (Ephemeroptera, Trichoptera, Plecoptera, and Chironomidae) in Finland, other studies often found low concordance in the structure and species richness in freshwater ecosystems, especially at small spatial scales (e.g. within basin Allen et al, 1999;Paavola et al, 2003;Tolonen et al, 2005). Low concordance can arise between similar-sized organisms, such as different groups of aquatic insects, because of specific requirements to use of the environment.…”
Section: Discussionmentioning
confidence: 93%